2014
DOI: 10.1111/jre.12238
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses the inflammatory responses of human gingival epithelial cells in a SIRT1 independent manner

Abstract: Resveratrol suppressed the inflammatory responses of P. gingivalis-stimulated HGECs, probably by inhibiting NF-κB signaling but independent of SIRT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
2
20
1
Order By: Relevance
“…This implies that the effect of resveratrol on inflammatory responses is mediated through a SIR1‐independent mechanism. In support of this idea, it has been demonstrated that resveratrol could suppress the inflammatory responses via NF‐κB, but not SIRT1 in human gingival epithelial and mouse embryonic fibroblasts [Kitada et al, ; Zagotta et al, ; Minagawa et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the effect of resveratrol on inflammatory responses is mediated through a SIR1‐independent mechanism. In support of this idea, it has been demonstrated that resveratrol could suppress the inflammatory responses via NF‐κB, but not SIRT1 in human gingival epithelial and mouse embryonic fibroblasts [Kitada et al, ; Zagotta et al, ; Minagawa et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the level of this cytokine is significantly higher in gingival crevicular fluid from patients with chronic periodontitis than in healthy individuals, and decreases following periodontal treatments (Turer, Durmus, Balli, & Guven, 2017;Zhang, Chen, Zhu, & Yan, 2016). In recent studies, resveratrol was also found to decrease the production and expression of P. gingivalis LPS-induced proinflammatory cytokines in human periodontal ligament cells (Phoolcharoena et al, 2013;Rizzo et al, 2012) and human gingival epithelial cells (Minagawa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is found in grapes and red wine at concentrations of the μg/g and mg/glass order, respectively, and has been shown to exhibit anti‐inflammatory properties in IL‐1β‐stimulated epithelial cells or LPS‐stimulated periodontal ligament cells and rodent models (Baur et al., ; Donnelly et al., ; Pearson et al., ; Rizzo et al., ). We have previously shown that resveratrol strongly inhibits the inflammatory response in human gingival epithelial cells stimulated with Porphyromonas gingivalis by suppressing NF‐κB translocation (Minagawa et al., ). It has also been reported that resveratrol prevents the RANKL‐induced osteoclast differentiation of RAW 264.7 cells, possibly through suppression of reactive oxygen species production (He, Andersson, Lindgren, & Li, ).…”
Section: Introductionmentioning
confidence: 99%